The Discussion of Job-related Problems in German-Lithuanian Business Calls / Die Behandlung von arbeitsbezogenen Problemen in deutsch-litauischen Geschäftstelefonaten - Eidukevičienė, Rūta; Žvaliauskienė, Sidona (Kalbotyra, 2015)
The article analyses German-Lithuanian business telephone communication, the topic that so far has not been taken up in any discourse studies in Lithuania. The corpus of data consists of 42 telephone calls in institutional settings. Specifically, it focuses on authentic German-Lithuanian business telephone calls whose aim is to discuss an important job-related problem. Telephone calls are an integral part of internal communication between a German employee of the parent company in Germany and a Lithuanian colleague in the Lithuanian branch. The analysis of the data follows the methodology of a traditional American model of conversational analysis (CA) supplementing it with the method of action patterns (Handlungsmusteranalyse), which was developed in the German-speaking research area. Based on this methodology, the analysis reconstructs the sequential structure of the telephone calls, identifies the communicative goals of the participants in each communication stage, and discusses the mechanism of handling job-related issues. In addition, the article investigates how the institutional and intercultural contexts influence the communication between the participants and to what extent they interpret these contexts as relevant for their professional interaction. Abstract in German